1994
DOI: 10.1002/j.1460-2075.1994.tb06944.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequences required for enhancer blocking activity of scs are located within two nuclease-hypersensitive regions.

Abstract: The Drosophila 87A7 heat shock locus is bordered, on the proximal and distal sides, by two special chromatin structures, scs and scs‘. Each structure is characterized by two sets of nuclease‐hypersensitive sites, located within moderately G/C‐rich DNA, flanking an A/T‐rich nuclease‐resistant region. scs and scs’ have been shown to insulate a white reporter gene from position effects and to prevent enhancer‐promoter interactions. These and other properties suggest scs and scs’ might function as chromatin domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
101
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 50 publications
8
101
0
1
Order By: Relevance
“…It is our sense that part of the reason for our success is the use of boundary elements to minimize position effects of random insertions (9,10,(16)(17)(18)(19). In this report, we insulate only the TA expression cassette and do not insulate the target.…”
Section: Discussionmentioning
confidence: 99%
“…It is our sense that part of the reason for our success is the use of boundary elements to minimize position effects of random insertions (9,10,(16)(17)(18)(19). In this report, we insulate only the TA expression cassette and do not insulate the target.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that they are associated with constitutive HS sites and establish higher-order domains of chromatin that affect the interaction between enhancers and promoters (9,20). For example, the "specialized chromatin structures" at the boundaries of the Drosophila hsp70 genes, which are associated with multiple DNase I HS sites, can insulate the white gene from both positive and negative chromosomal position effects and can insulate the hsp70 promoter from activation by enhancers (29,55). Specific peptides (BEAF-32A and BEAF-32B) are constitutively bound to these elements, and immunostaining localizes these factors to interband regions and puffs of polytene chromosomes, suggesting a role in the organization of chromosomal domains (25,60).…”
Section: Discussionmentioning
confidence: 99%
“…A search of FlyBase reveals that other investigators have used this sequence as a compatible promoter in their constructs as well. Because IRA of the hsp70 locus is maintained by insulating domain boundaries (Kellum and Schedl 1991;Kellum and Schedl 1992;Vasquez and Schedl 1994) and not promoter specificity, it is possible that this promoter needs only to mediate efficient initiation without concern for intergenic enhancer interactions. Although the normal hsp 70 promoter maintains a paused RNA polymerase downstream of its start site (Lis and Wu 1993), the small portion of the promoter that we used in oafSWAp lacks critical sequences required for generating the paused complex (Lee et al 1992).…”
Section: Promoter Promiscuitymentioning
confidence: 99%
“…In vertebrates, these include the locus control region (LCR) of the globin gene cluster (Forrester et al 1986;Grosveld et al 1987;Chung et al 1993) and the A elements of the lysozyme gene (Stief et al 1989;Bonifer et al 1990;McKnight et al 1992). In Drosophila, domain element characteristics are associated with the specialized chromatin structures scs and scs' of the hsp70 locus (Kellum and Schedl 1991;Vasquez and Schedl 1994) and the su(Hw) binding regron within the gypsy re trotransposon (Holdridge and Dorsett 1991;Geyer and Corces 1992;Roseman et al 1993). Most of these domain elements can also act ectopically as insulators to prevent enhancers on one side from acting on promoters on the other side (Stief et al 1989;Kellum and Schedl 1992;Chung et al 1993;Cai and Levine 1995;Scott and Geyer 1995).…”
mentioning
confidence: 99%